STAKEHOLDER ENGAGEMENT DALAM PROMOSI DESTINASI PARIWISATA INDONESIA TAHUN 2020-2022: ANALISIS HASHTAG TWITTER #DIINDONESIAAJA - Sanda Rieke Kuntadi; Nurul Dwi Purwanti (JURNAL MASTER PARIWISATA, 2023)
The research was conducted to analyze stakeholder engagement in using the hashtag #DiIndonesiaAja on Twitter social media in 2020-2021 and in 2022.The data in this study were collected by the web crawling method, virtual observation on Twitter social media, and hashtag searches through the Social Searcher website. Based on the data obtained, there were 1.013 stakeholder who made the upload by embedding the hashtag #DiIndonesiaAja. Qualitative analysis was conducted to identify the position of stakeholders who are involved in using the hashtag #DiIndonesiaAja on social media Twitter based on the ratings for support and ratings for receptiveness measurement. The results showed that there were 3,878 tweets which has been made by stakeholders by using hashtag #DiIndonesiaAja. From the results of data collection, the hashtag #DiIndonesiaAja was most widely used in November 2020. Meanwhile, hashtag #DiIndonesiaAja was least used in July 2020. The research that conducts analysis based on social media uses web crawling techniques aims to contribute and provide input for future tourism destination promotion policies, particularly for the Ministry of Tourism and Creative Economy of Republic Indonesia, in efforts to develop and plan tourism destination promotion policies and programs using social media platforms. Keywords: stakeholder engagement, stakeholder identification, social media, tourism.